Observer-based adaptive robust control of aircraft antiskid brakes with disturbance compensation - Wang, Zhuangzhuang; Bai, Ning; Liu, Xiaochao; Qi, Pengyuan (Control engineering practice, 2024)
The efficient antiskid braking control of aircraft is achieved by accurately tracking the optimal slip ratio. However, aircraft antiskid braking systems are subject to many parametric uncertainties and uncertain disturbances, and the limited sensor signals make it more difficult to design a high-performance antiskid braking system controller. To address this issue, an observer-based adaptive robust aircraft antiskid braking system controller with disturbance compensation is proposed to enhance the tracking performance and disturbance rejection of aircraft antiskid braking system. The proposed controller effectively integrates parameter identification, adaptive control, and extended state observer using the backstepping method. Parametric uncertainties and fast time-varying brake torque conversion coefficient are handled by adaptive law and least squares parameter identification method, respectively. After that, the remaining parametric uncertainties, parameter identification errors, and uncertain disturbances are observed integrally by constructing extended state observer and compensated in a feedforward way. Another feature of the designed controller is that the dynamics of the hydraulic system are considered, and the disturbances of the hydraulic system are also observed and compensated with extended state observer, thus further improving tracking accuracy. Since the burden of extended state observer is greatly reduced by adaptive law and parameter identification, the proposed controller can effectively avoid high-gain feedback while theoretically guaranteeing that the tracking error is bounded in the presence of time-variant uncertainties. The effectiveness of the proposed controller is proved by several sets of simulation tests and brake testing platform experiments. •An observer-based aircraft ABS controller with disturbance compensation is proposed.•Fast time-varying uncertain parameters in aircraft ABS are handled separately by RLS.•Disturbances in wheel and hydraulic dynamics are estimated and actively compensated.•Parameter identification, adaptive control and ESO are effectively integrated.